Products of vitamin D3 or 7-dehydrocholesterol metabolism by cytochrome P450scc show anti-leukemia effects, having low or absent calcemic activity. - Andrzej T Slominski; Zorica Janjetovic; Brian E Fuller; Michal A Zmijewski; Robert C Tuckey; Minh N Nguyen; Trevor Sweatman; Wei Li; Jordan Zjawiony; Duane Miller; Tai C Chen; Gerard Lozanski; et al. (PLoS ONE)
Background Cytochrome P450scc metabolizes vitamin D3 to 20-hydroxyvitamin D3 (20(OH)D3) and 20,23(OH)(2)D3, as well as 1-hydroxyvitamin D3 to 1alpha,20-dihydroxyvitamin D3 (1,20(OH)(2)D3). It also cleaves the side chain of 7-dehydrocholesterol producing 7-dehydropregnenolone (7DHP), which can be transformed to 20(OH)7DHP. UVB induces transformation of the steroidal 5,7-dienes to pregnacalciferol (pD) and a lumisterol-like compounds (pL). Methods and findings To define the biological significance of these P450scc-initiated pathways, we tested the effects of their 5,7-diene precursors and secosteroidal products on leukemia cell differentiation and proliferation in comparison to 1alpha,25-dihydroxyvitamin D3 (1,25(OH)(2)D3). These secosteroids inhibited proliferation and induced erythroid differentiation of K562 human chronic myeloid and MEL mouse leukemia cells with 20(OH)D3 and 20,23(OH)(2)D3 being either equipotent or slightly less potent than 1,25(OH)(2)D3, while 1,20(OH)(2)D3, pD and pL compounds were slightly or moderately less potent. The compounds also inhibited proliferation and induced monocytic differentiation of HL-60 promyelocytic and U937 promonocytic human leukemia cells. Among them 1,25(OH)(2)D3 was the most potent, 20(OH)D3, 20,23(OH)(2)D3 and 1,20(OH)(2)D3 were less active, and pD and pL compounds were the least potent. Since it had been previously proven that secosteroids without the side chain (pD) have no effect on systemic calcium levels we performed additional testing in rats and found that 20(OH)D3 had no calcemic activity at concentration as high as 1 microg/kg, whereas, 1,20(OH)(2)D3 was slightly to moderately calcemic and 1,25(OH)(2)D3 had strong calcemic activity. Conclusions We identified novel secosteroids that are excellent candidates for anti-leukemia therapy with 20(OH)D3 deserving special attention because of its relatively high potency and lack of calcemic activity.